A Novel MicroRNA and the Target Gene TAB2 Can Regulate the Process of Sucking Blood in and the Spawn Rate of Hyalomma asiaticum (Acari: Ixodidae) Ticks - Luo, Jin; Wu, Feng; Liu, Wenge; Ren, Qiaoyun; Diao, Peiwen; Guan, Guiquan; Luo, Jianxun; Yin, Hong; Liu, Guangyuan (Frontiers in Immunology, 2022)
Ticks are blood-sucking parasites that are harmful to humans and animals. MicroRNAs are a class of conserved small noncoding RNAs that play regulatory roles in the expression of many genes at the posttranscriptional level. Here, a novel miRNA (nov-miR-17) was identified from a small RNA data library of Hyalomma asiaticum by next-generation sequencing. PCR was used to obtain precursor nov-miR-17 by RACE using mature loop primers. The secondary structure was predicted with UNAFold. The interaction of nov-miR-17 with its target gene TAB2 was predicted using RNAhybrid software and identified in vitro by luciferase assays. Moreover, the interaction was confirmed in vivo by phenotype rescue experiments in which dsTAB2 was used for RNA interference (RNAi) and an antagomir of nov-miR-17 was used for miRNA silencing. The expression levels of nov-miR-17 and TAB2 in ticks at different developmental stages and the expression of nov-miR-17 in different tissues were analyzed by real-time qPCR. All data were analyzed using GraphPad Prism version 5. Results: The results showed that TAB2 was a target gene of nov-miR-17. When the blood-sucking process of larval, nymph and adult ticks was prolonged, the expression of nov-miR-17 was decreased, and TAB2 expression was increased. However, the level of nov-miR-17 in the midgut of engorged ticks was highest at all stages. Therefore, nov-miR-17 plays an important role in the blood-sucking process. The overexpression of nov-miR-17 indicated that this miRNA affected the engorged weight (P < 0.001) and spawn rate (P < 0.001) of female ticks. RNAi of TAB2 also had the same effect. dsRNA not only impacted the weight (P < 0.01) but also reduced the spawn rate (P < 0.001) of the ticks. Furthermore, significant recovery was observed in nov-miR-17-silenced ticks after TAB2 silencing by RNAi. nov-miR-17 silencing by antagomir not only impacted the engorged weight of the female ticks (P < 0.001) but also the number of days that the females needed to progress from engorgement to spawning (P < 0.001). The study showed that nov-miR-17, as a new miRNA, plays an important role along with its target gene TAB2 in the blood-sucking and spawning processes in female ticks.